Legal Analysis of the Relationship between BPN Decree Number 3/Pbt.36/III/2023 and Supreme Court Decision Number 250 PK/Pdt/2004 Jo. 82/Pdt.G/1997/PN.TNG in the Cancellation of Transfer of Land Rights - Blezinzky, Lavisya Nadiya; Dewi , Amelia Sri Kusuma; Supriyadi, Supriyadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
The legal conflict between BPN Decree Number 3/Pbt.36/III/2023 and Supreme Court Decision Number 250 PK/Pdt/2004 Jo. 82/Pdt.G/1997/PN.TNG creates uncertainty in the implementation of land rights that should have been resolved through the courts. This problem shows the disharmony between the administrative authority of the land institution and the permanent legal force possessed by the court decision. When a court decision that has permanent legal force is not respected by the administrative institution, there is a vacuum of legal protection for parties who have legally obtained their rights. Therefore, this study is important because it concerns the principle of res judicata and the obligation of state administrative institutions, in this case BPN, to submit to and obey court decisions that are final and binding. This study uses a normative legal approach method with qualitative analysis techniques on various relevant legal instruments. Data were collected through literature studies and analyzed descriptively-analystically. The results of the study indicate that the BPN's action in issuing Decree Number 3/Pbt.36/III/2023 is a form of ultra vires, because it directly contradicts the Supreme Court Decision which has permanent legal force. This can be qualified as a form of abuse of authority that not only violates the principle of legality, but also damages the authority of the judicial institution. As a result, this situation opens up opportunities for the aggrieved party to take legal action through administrative objections, lawsuits to the State Administrative Court (TUN), or reports to the Indonesian Ombudsman for alleged maladministration. In conclusion, harmonization between land administration law and civil procedural law is very necessary to ensure the consistency of legal decisions and administrative actions, in order to realize legal certainty, protection of rights, and substantive justice in the national land system.